Kewenangan KPK Untuk Menyidik Anggota TNI Bersama-Sama Dengan Sipil Secara Koneksitas - Gaol, Yulinda Regina C. Lumban; Syahrir, Alvi; Ikhsan, Edy; Trisna, Wessy (Dinasti Review Publisher, 2024)
Based on article 42 of Law Number 30 of 2002, KPK is given authority to coordinate and control investigation and prosecution of criminal cases of corruption carried out jointly by persons subject to the General and Military Court. However, KPK encounters problems in investigating TNI members together with civilians, as happened in the Basarnas case. This normative legal research uses statute approach and conceptual approach, in order to provide a view for harmonization of regulations related to the KPK's connectivity authority. The results show that it is necessary to change the definition of